O'Reilly Infrastructure & Ops Superstream Series : Security Edition 9/23/2020 - Newman, Sam; Rice, Liz; Janca, Tanya; Paxton-Fear, Katie; Stella, Josh (O'Reilly Media, Incorporated, 2020)
About the Infrastructure and Ops Superstream Series : This four-part series of half-day online events covers the most challenging and promising topics facing those working in infrastructure and operations today: site reliability engineering, security, Kubernetes, and microservices. Security is everyone's responsibility. These sessions will get you up to speed with key techniques and best practices for securing your applications, systems, and organization. Discover how to better assess threats and develop a security-aware mindset. Learn how to detect and prevent risks and find application vulnerabilities. And explore pragmatic approaches for adding security to your delivery pipeline. What you'll learn-and how you can apply it Explore the fundamentals of security, including how to improve security within your organization Learn how to assess potential security risks that could affect your deployments with containers Understand how security should work with DevOps Discover how to evaluate your cloud environment for misconfiguration vulnerabilities and address them without slowing down innovation or removing the power that cloud computing delivers This Superstream is for you because ... You're a developer new to or looking to enter a security role. You want to learn about DevSecOps. You want to get started with bug hunting. You want to become well-versed in the foundations and best practices of security. Prerequisites: Come with your questions Have a pen and paper handy to capture notes, insights, and inspiration Recommended follow-up: Read Container Security (book) Read Web Application Security (book) Read Practical Cloud Security (book) Take Windows Network Security Fundamentals (live online training course with Glenn Weadock).